LABOUR PRODUCTIVITY IN THE CROATIAN CONSTRUCTION INDUSTRY: IMPACT FACTORS FROM THE CLIENT’S POINT OF VIEW (Advances in Civil and Architectural Engineering, 2021)
Worker productivity impact factors are one of the most important success factors in the construction industry. Understanding the workers' personality and competence, measuring it and taking appropriate action can directly contribute and facilitate the goals of construction projects. Each worker has their own personality, perception, ability, and so on; they also have different expectations at work. In this paper, the previous researchers of impact factors for labour productivity from the client’s point of view are briefly analysed. New research in Croatia was conducted and research from the United States and Turkey has been summarised. The differences in research methodologies are also explained. The US study included 40 factors that influence productivity of labour. The Turkish and Croatian studies were based on two groups of factors: economic and socio-psychological factors, 17 factors in total. The main contribution is the qualitative analysis and comparison of the research results in Croatia and Turkey. The economic factors are currently more important than socio-psychological ones in Croatia and Turkey. Knowing the importance of the factors for increasing productivity is the starting point for acting towards the successful realisation of a project. Therefore, further research and focus on this theme are very welcomed.